Laporan Kasus: Pembesaran gingiva yang diinduksi fenitoin - Rinawati Satrio; Primarizka Iswara Laksmi (Fakultas Kedokteran Gigi Universitas Jember, 2018)
Gingival enlargement is a kind of oral manifestation, that can caused by induction of anticonvulsant drugs. Phenytoin is one of anticonvulsant drug that can caused gingival enlargement. Gingival enlargement in this case developed until grade III. The patient was highly phenytoin dependent and can’t be reconciled. The aim of this paper is to find out the cause of phenytoin induced gingival enlargement and its treatment. A 20 years old woman came to RSGM UNSOED to check her swollen gums. The patient’s history was epilepsy and had been regularly taking phenytoin. The patient was taking 30 mg phenobarbital, 10 mg clobazam, 1 mg folic acid and 100 mg phenytoin 2 times a day with 2 capsules each time that had been consumted for 4 years. Phenytoin as anticonvulsant drug has side effects that can caused gingival enlargement, this is because phenytoin can increase extracellular connective tissue, collagen and fibrous.